2018
DOI: 10.1007/s00068-018-0978-8
|View full text |Cite
|
Sign up to set email alerts
|

Pre-hospital rescue times and interventions in severe trauma in Germany and the Netherlands: a matched-pairs analysis

Abstract: Multiple differences and some similarities in the treatment of major trauma patients with similar injury patterns were found but no clinically relevant differences in the chosen outcome parameters could be observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…18 This time interval difference was smaller for patients with an ISS of ≥16, with 61 minutes for the Dutch group and 66 minutes for their German counterparts. 19 However, Timm et al 19 did not find clinically relevant differences in outcome parameters of severely injured patients that could be accounted for this 5-minute advantage in favor of the Dutch.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…18 This time interval difference was smaller for patients with an ISS of ≥16, with 61 minutes for the Dutch group and 66 minutes for their German counterparts. 19 However, Timm et al 19 did not find clinically relevant differences in outcome parameters of severely injured patients that could be accounted for this 5-minute advantage in favor of the Dutch.…”
Section: Discussionmentioning
confidence: 96%
“…20 It is unclear whether German policies on withdrawal of life-sustaining treatment differ from the Dutch policies. However, an international comparison study by Timm et al 19 reported that 3.8% of German patients surviving a severe injury (ISS, ≥16) had a "persistent vegetative state" as an outcome, whereas this was only 0.7% in the Netherlands. An international comparison study is needed to assess these national dissimilarities fully.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with our previous data on outcome in patients with moderate to severe isolated TBI [ 24 ]. Interestingly, a comparison study between Germany and the Netherlands in severe trauma patients revealed an almost none-existing rate of Dutch patients with persistent vegetative state compared to 4% in German patients [ 25 ]. We have previously speculated that these differences may be partly due to cultural differences [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Time of arrival since trauma was not registered. Previous studies in this region showed that patients arrive at the hospital between 20 and 60 min after trauma [17,18]. Blood is drawn within 10 min after presentation at the trauma bay and directly placed in the flow cytometer.…”
Section: Study Proceduresmentioning
confidence: 99%